Selective estrogen receptor modulator: efficacy in abnormal uterine bleeding in perimenopausal women - Mani, Ankita; Sharma, Kanchan; Kumar, Arun; Talukdar, R. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Abnormal uterine bleeding affects 50% women of perimenopausal age group. The use of ormeloxifene (SERMS) in management of AUB is well known. The objective of the present study was aimed to see the effects of ormeloxifene on different types of endometrium.in the medical management of Abnormal Uterine Bleeding (AUB). Methods: It was Prospective, interventional study. A total of 90 women who attended Outpatient Gynaecology Department, Guwahati with complain of AUB in perimenopausal age group (37-48) were prescribed 60mg ormeloxifene twice weekly for 3 months followed by once weekly for next 3 months after preliminary D and C. Results: Ormeloxifene was found to be more effective in reducing PBAC score and ET in patients with proliferative and secretory endometrium The reduction in mean PBAC score with ormeloxifene (175.3 to 20.93)(p value 0.0001) and ET (9.6 to 2.9 mm) (p value 0.0001) in proliferative endometrium, (179.2 to 14.8 (p value 0.0001) ) and ET 11.1 to 1.9 mm (p value 0.0003)in secretory endometrium was observed after 6 months. However, it was found not to be effective in reducing PBAC score and ET in patients with atrophic endometrium. Change in PBAC SCORE from 176.4 to 150.8 (p value 0.08) and in ET from 2.8 to 2.1mm( p value 0.3) was observed. No major side effects were reported. Conclusions: Ormeloxifene is effective in AUB with proliferative and secretory endometrium.